Terahertz spectroscopy of bacteriorhodopsin and rhodopsin: Similarities and differences - Balu, R.; Zhang, H.; Zukowski, E.; Chen, J. Y.; Markelz, A. G.; Gregurick, S. K. (Biophysical Journal, 2008)
We studied the low-frequency terahertz spectroscopy of two photoactive protein systems, rhodopsin and bacteriorhodopsin, as a means to characterize collective low-frequency motions in helical transmembrane proteins. From this work, we found that the nature of the vibrational motions activated by terahertz radiation is surprisingly similar between these two structurally similar proteins. Specifically, at the lowest frequencies probed, the cytoplasmic loop regions of the proteins are highly active; and at the higher terahertz frequencies studied, the extracellular loop regions of the protein systems become vibrationally activated. In the case of bacteriorhodopsin, the calculated terahertz spectra are compared with the experimental terahertz signature. This work illustrates the importance of terahertz spectroscopy to identify vibrational degrees of freedom which correlate to known conformational changes in these proteins.
Keywords: Biophysics; bovine rhodopsin; conformational-changes; elastic; frequency normal-modes; light activation; molecular-dynamics simulation; neutron-scattering; protein-coupled receptors; transmembrane helices; vibrational-modes; wild-type